Related factor of Knowledge by Stroke in Institute of Higher Education Employees - Novida Rizky Wardhani; Santi Martini (Universitas Airlangga, 2014)
Stroke is a non-communicable disease that causes death in the top ranks in urban areas which around 28.5% in Indonesia at 2011. Strokes begin at the productive age. This study aims to determine factors associated with knowledge about stroke in workers of educational institutions in Surabaya. This type of research is an observation analytic study using a cross-sectional study design. The questionnaire was given to 142 respondents. Dependent variables in this study were knowledge of stroke risk factors, level of initial stroke recognition, and how to handle it. The independent variables are age, sex, and level of education. Data analysis using chi-square test and spearman test. The results showed a level of knowledge of stroke risk factors 78.9% of respondents in the level of